Large-scale ocean circulation in the Southern Hemisphere with closed and open Drake Passage – A laboratory minimal model approach. (February 2019) - Bozóki, Tamás; Czelnai, Levente; Horicsányi, Attila; Nyerges, Anita; Pál, András; Pálfy, József; Vincze, Miklós
Abstract: We report on a laboratory model of the large-scale flow phenomena in the Southern Ocean with a closed Drake Passage, imitating the situation before the Eocene-Oligocene transition (EOT) ca. 34 million years ago. In a differentially heated rotating annular wave tank an insulating 'meridional' barrier is installed to block zonal circulation. The obtained temperature fields and time series are compared to the ones from control runs with partially blocked and fully opened 'passages'. In the 'closed' case a persistent azimuthal temperature gradient emerges whose magnitude scales linearly with the 'meridional' temperature contrast. The anomalous temperature distribution is accompanied with perturbations of the background flow yielding significantly larger low frequency variability than in the 'opened' configuration. The experimental findings have implications to the EOT but at present validation of results is hindered by the lack of deep-sea drilling data from the Southeast Pacific and adjacent parts of the Southern Ocean. Our model may inspire further paleoceanographic research in this largely unexplored region.